A Protocol Guide for the N. crassa Yeast Artificial Chromosome Library - M. B. Centola; C. T. Yamashiro; L. S. Martel; J. C. Royer; T. J. Schmidhauser (Fungal Genetics Reports, 1994)
A yeast artificial chromosome (YAC) library of Neurospora crassa strain 74-OR23-1A has been constructed. This library has been used to clone 750 kb of contiguous DNA sequences from the centromere region of linkage group VII (M. Centola and J. Carbon. 1994. Mol. Cell. Biol. 14:1510-1519). The purpose of this article is explicitly to outline procedures that have been developed for library screening and chromosome walking.